Wnt antagonist DKK‐1 levels in systemic sclerosis are lower in skin but not in blood and are regulated by microRNA33a‐3p. Issue 1 (10th September 2020) - Henderson, John; Pryzborski, Stefan; Stratton, Richard; O'Reilly, Steven
Abstract: Background: Systemic sclerosis is an autoimmune skin disease which is associated with inflammation and resulting skin fibrosis. Myofibroblasts are the key cell type associated with the fibrosis but how they are differentiated is not clear. DKK‐1 is a Wnt antagonist that blocks Wnt‐mediated fibrosis and is reduced in fibrotic conditions. Thus, DKK‐1 is a clear negative regulator of fibrosis in systemic sclerosis and its regulation is unknown. The aim of this work is to determine the levels of DKK‐1 in serum and tissues of SSc and its regulation. Methods: Skin biopsies were taken from early diffuse systemic sclerosis patients and healthy controls and DKK‐1 measured by ELISA; serum was also isolated and DKK‐1 quantified. DKK‐1 was also measured by qRT‐PCR. MicroRNA33a‐3p was measured by TaqMan PCR. miR mimics and controls were transfected into dermal fibroblasts. Bleomycin mouse model was employed and compared to vehicle control treated mice, and gene expression was employed for DKK‐1 and various extracellular matrix genes. Results: DKK‐1 is reduced in SSc skin and fibroblasts but is not reduced in the circulation in patients. MicroRNA33a‐3p regulates DKK‐1 levels epigenetically and is significantly reduced in SSc cells and whole tissue. DKK‐1 is also reduced in the bleomycin mouse model and pro‐fibrotic genes elevated. Conclusion: DKK‐1 is reduced in SSc cells and is regulated by miR33a‐3p, and restoring DKK‐1 levels through epigenetic means could be a therapeutic target in systemic sclerosis.